DESCRIPTION OF THE ROLE OF DRUG SWALLOWING (PMO) SUPERVISION ON THE SUCCESS OF TUBERCULOSIS TREATMENT AT THE SIKUMANA PUBLIC HEALTH CENTER IN KUPANG CITY - Anin, Yeni Anjelina; Ndun, Helga J. N.; Gustam, Tasalina Y. P.; Limbu, Ribka (HEARTY, 2026)
Tuberculosis (TB) is an infectious disease caused by the bacteria Mycobacterium tuberculosis and can be fatal if not treated properly. This qualitative study with a phenomenological approach aims to determine the role of Drug Supervisors (PMO) in the success of TB treatment at the Sikumana Community Health Center in Kupang City. This study involved 16 informants selected using a purposive sampling technique. The results of the study indicate that PMOs play an important role in the success of TB treatment through several roles, namely the role of supervision by monitoring the medication schedule, ensuring the availability of drugs and supervising it is important, especially for children, the role of motivation by knowing and addressing the side effects of OAT, motivating patients to comply with taking medication, reaffirming the symptoms and impacts of not taking OAT, the role of reminders by helping and reminding patients to take OAT at the community health center and sputum examination to monitor the progress of treatment, by helping or accompanying PMOs to discuss with health workers and the role of education by providing education about TB, treatment methods, and prevention of transmission.